Ageing and exercise‐induced motor unit remodelling. (29th March 2022) - Jones, Eleanor J.; Chiou, Shin‐Yi; Atherton, Philip J.; Phillips, Bethan E.; Piasecki, Mathew
Abstract: A motor unit (MU) comprises the neuron cell body, its corresponding axon and each of the muscle fibres it innervates. Many studies highlight age‐related reductions in the number of MUs, yet the ability of a MU to undergo remodelling and to expand to rescue denervated muscle fibres is also a defining feature of MU plasticity. Remodelling of MUs involves two coordinated processes: (i) axonal sprouting and new branching growth from adjacent surviving neurons, and (ii) the formation of key structures around the neuromuscular junction to resume muscle–nerve communication. These processes rely on neurotrophins and coordinated signalling in muscle–nerve interactions. To date, several neurotrophins have attracted focus in animal models, including brain‐derived neurotrophic factor and insulin‐like growth factors I and II. Exercise in older age has demonstrated benefits in multiple physiological systems including skeletal muscle, yet evidence suggests this may also extend to peripheral MU remodelling. There is, however, a lack of research in humans due to methodological limitations which are easily surmountable in animal models. To improve mechanistic insight of the effects of exercise on MU remodelling with advancing age, future research should focus on combining methodological approaches to explore the in vivo physiological function of the MU alongside alterations of the localised molecular environment. Abstract : Abstract figure legend Ageing is associated with a loss of motoneurons, which results in the denervation of motor unit muscle fibres and their inability to contract. Several lines of evidence from human and animal models have now highlighted the role of exercise in improving reinnervation capacity and the rescue of denervated fibres, presumably acting to preserve fibre number and total muscle function.